Hepatectomia regrada e colectomia esquerda simultâneas realizadas por acesso laparoscópico - Lupinacci, Renato Micelli [UNESP] (2011)
Laparoscopic approaches have been increasingly used in patients with colorectal or liver cancer. Simultaneous colectomy and hepatectomy are considered safe techniques and present similar oncological results regardless of the location of the primary tumor when there are fewer than four liver metastases, since there is no increase in morbidity or decrease in survival. The development of laparoscopic techniques and materials has made the combined resection of the colon and liver a very attractive option. The aim of this study is to demonstrate the synchronous resection of the sigmoid tumor and single liver metastasis treated by purely laparoscopic colectomy and liver left lateral sectorectomy.